Dados de equilíbrio de fases a altas pressões para sistemas sintéticos e amostras de petróleo - Ferreira, Fedra Alexandra de Sousa Vaquero Marado (2018)
The extreme conditions of pressure, temperature and carbon dioxide composition present in the pre-salt deposits are a challenge related to the exploration and production of these reservoirs. In the context of high compositions of carbon dioxide, in recent years its use in the tertiary recovery of petroleum has been gaining expression and research in this area is necessary for greater knowledge of the process and ideal conditions for its injection. Thus, this work aims the study of the phase behavior at high pressures of synthetic and representative systems of petroleum. A high pressure phase equilibrium cell, that allows a range of pressure between 6 and 30 MPa and temperatures up to 393 K, based on synthetic visual method, was used for the PVT study. This cell was also used for PVT data determination using the non-visual synthetic method, i. e., phase transition determination by volume cell variation. The research was divided in two stages. In the first stage, binary systems (CO2 + cyclohexene and CO2 + squalane) were studied with CO2 molar fraction composition between 0,30 and 0,85, experiment temperatures between 303 and 393 K and bubble pressures observed in a range of 5,5 and 19,7 MPa and a ternary system (CO2 + cyclohexene + squalane) representative of an oil sample were studied with CO2 molar fraction composition between 0,23 and 0,64, squalane molar fraction in a range of 0,01 and 0,20, experiment temperatures between 303 and 393 K and bubble pressures observed in a range of 3,2 and 13,0 MPa. In the second stage two real samples were characterized and fractionated, one being condensate gas and the other being light petroleum and later used in the study of phase behavior. The binary systems: CO2 + condensate gas was studied in CO2 molar fractions between 0,40 and 0,80, range of temperatures of 313 up to 393 K and the bubble pressures ranged between 6,3 and 14,4 MPa. The binary system CO2 + light petroleum was studied in CO2 molar fractions between 0,40 and 0,80, range of temperatures of 313 up to 393 K and the bubble pressures ranged between 6,2 and 18,0 MPa . The thermodynamic modeling was done by applying the cubic state equation of Soave-ReidlichKwong, in the case of synthetic systems, with estimated parameters of Mathias and Copeman for the vapor phase and Van der Waals 2 mixing rule and for the real samples de equation of state of of Adachi-Lu-Sugie, with Van der Waals mixing rule 1 was applied. The thermodynamic modeling showed a good fit to the experimental data with mean deviations of less than 3%.